Think Stop before Going 'Off-Label' - Gerald Y Minuk (Canadian Journal of Gastroenterology)
Only after careful and extensive review of all available safety and efficacy data derived from preclinical and clinical trials will a regulatory body approve the licensing of a drug for a specific medical condition ('indication'). Experience with thalidomide, fialuridine and troglitazone, to name a few, reveal that despite these efforts, the process is not infallible. What then can we expect when a drug is used for a medical condition in which no such review process has been undertaken ('offlabel' use of the drug)?